Beginning Samsung ARTIK : a guide for developers - Wootton, Cliff (Technology in action series., 2016)
Discover which ARTIK modules to use for various applications, and how to produce code for them. This book goes beyond the information previously available online, efficiently guiding developers from initial setup of their development environment to product development and prototyping in no time. Beginners will find helpful background insights into foundation technology and useful reference information is included for more advanced developers. Samsung's announcement of the new ARTIK modules for IoT has generated tremendous interest in the developer market for wearable and other consumer or industrial devices. This book provides the perfect tutorial-based introduction to the ARTIK family of "Systems on Modules," which integrate powerful microprocessors, memory, wireless connectivity, and enhanced security on to very small form factor boards. With Beginning Samsung ARTIK as your guide, take the next steps to creating great solutions with an ARTIK. What You'll Learn Use terminal emulators to access the command line and talk to the device Establish Wi-Fi connectivity with a wireless network Upgrade the operating system and install additional software Bring up Eclipse IDE and create a cross-compiler toolchain on Mac OS X Cross-compile for the ARM processors in the ARTIK modules using Arduino IDE with libArduino to C Use C to access the ARTIK hardware via a file based API Use Node.js and Python inside the ARTIK module Integrate applications with the Samsung SAMI data aggregation hub Use Temboo to generate IoT software solutions that can be downloaded and compiled natively inside the ARTIK Debug applications with software and hardware probes Who This Book Is For Moderately experienced developers wanting to understand ARTIK and how to interact with it from within their own apps or web services. .